Influencing factors of employee brand equity from the perspective of FinTech - Lin, Lichao; Huang, Ziling; Jia, Xiaofei (Frontiers in Psychology, 2022)
Recent years have seen a heated discussion on what influences employees’ recognition of enterprise brand equity among the psychological community. Some empirical evidence suggests that the brand equity of consumers and brand equity of sales are two categories that should be studied. However, more recent discussions have focused more on the former. In contrast, this study discusses the factors influencing brand equity based on the employee level. Moreover, this paper examines whether FinTech can help companies get out of financing difficulties and thus improve employees’ brand equity recognition. This research illustrates how FinTech has become an essential driver of brand equity value. Based on micro panel data on enterprises from 2011 to 2019, we analyze the transmission mechanism between the two factors and the mediating role of financing constraints. FinTech’s development promotes employees’ recognition of corporate brand equity, and financing constraints are an essential transmission path between the two factors. Furthermore, the impact of financing constraints on employee brand equity identity is characterized by cross-regional economic heterogeneity. In contrast, the development of FinTech characterizes the cross-enterprise heterogeneity in employees’ recognition of brand equity value. Altogether, this study demonstrates the promising application of FinTech in influencing the mechanisms of employee brand equity.